Análise das estruturas da capacidade pública de inovação do Programa inova Maranhão no período de 2019 a 2023 - MOUSINHO, Greice kely Ferreira Silva (2024)
This study investigates the public innovation capabilities of the Inova Maranhão Program, considering the results of the FIEC State Innovation Indicator and innovation actions, within the perspectives of R&D and CT&I in the period from 2019 to 2023. To achieve this objective, a bibliographic review of official documents was carried out, a scripted interview with one of the superintendents of the State Secretariat for Science, Technology and Innovation (SECTI) and a collection of primary data with the agency. The research is based on a review of the literature on innovation and development, combined with a structured analysis of the public policies and programs implemented in the Inova Maranhão Program. The intention is to understand the role of the State in promoting innovation as a driver of economic and social development, identifying the advances that have occurred and the elements necessary for an adequate structure of public innovation capabilities. The analysis of public policies and programs implemented between 2019 and 2023 reveals progress in structuring the invocation policy, but also identifies that the public capacity to establish public-private partnerships needs more ambitious goals, as well as other challenges and opportunities highlighted in the results that contribute to strengthening the local innovation ecosystem. The results of this research contribute, through the analysis and evaluation of the elements of public capacity, to the debate on public innovation policies in Maranhão and offer subsidies for the formulation of more effective development strategies for the Inova Maranhão program.